The patient’s voice: a cross-sectional study of physical health and disability in juvenile idiopathic arthritis - Sofie Mikalsen Arneng; Isabelle Pignatel Jenssen; Anette Lundestad; Lena Cetrelli; Oskar Angenete; Ellen Nordal; Karin B. Tylleskär; Pål Richard Romundstad; Marite Rygg (Pediatric Rheumatology Online Journal)
Abstract Background With increasing focus on patient-reported outcome measures (PROMs) in chronic rheumatic diseases, we aimed to evaluate the self-reported physical and psychosocial health in children with juvenile idiopathic arthritis (JIA) compared to matched population-based controls. Furthermore, we aimed to study the association of patient- and physician-reported outcome measures in JIA with patient-reported physical disability. Methods We used data from a Norwegian JIA cohort study (NorJIA), including clinical characteristics and outcome measures in participants with JIA and sex- and age-matched population-based controls. Self-reported physical and psychosocial health were assessed using the generic Child Health Questionnaire (CHQ). Comparisons between children with JIA and controls were performed by test of proportions for categorical variables and t-test for continuous variables. To evaluate the association of patient- and physician-reported outcome measures with patient-reported physical disability, assessed with the Child Health Assessment Questionnaire (CHAQ) in children with JIA, we used logistic regression to estimate adjusted odds ratio (OR) with 95% confidence interval (CI). Results In total, 221 participants with JIA (59.3% females, median age 12.7 years) and 207 controls with available data were included. In the JIA group, 24.3% scored below the norm for physical health (CHQ PhS < 40) and 8.7% scored below the norm for psychosocial health (CHQ PsS < 40). The corresponding numbers for the control group were 0.5% and 1.9%, respectively. In the JIA group, 57.9% reported physical disability (CHAQ > 0). Several patient-reported outcome measures, such as poor physical health (CHQ PhS < 40), disease-related pain, and the patient’s global assessment of disease impact on wellbeing, were strongly associated with self-reported physical disability (CHAQ > 0), adjusted OR 19.0 (95% CI 5.6, 64.1), 14.1 (95% CI 6.8, 29.2), and 14.0 (95% CI 6.2, 31.6), respectively. Associations were also found for active disease according to Wallace (adjusted OR 36.3, 95% CI 10.3, 128.1), and physician-reported global assessment of disease activity (adjusted OR 6.2, 95% CI 3.1, 12.6). Conclusions The strong association between patient- and physician-reported outcome measures and patient-reported physical disability strengthens the importance of including the patient’s voice in a comprehensive evaluation of patient outcome in JIA. Trial registration ClinicalTrials.gov (No: NCT03904459).